Financial Early Warning System Implementation Strategy for Clinics - Ahmad, Zulkifli; Sulistiyana, Catur Setiya; Purwadi, Purwadi; Yani, Yani (Jurnal Ekuisci, 2025)
Background. Clinics in the healthcare business face various challenges, especially in urban areas where competition with new clinics and large hospitals is intensifying. Continuously changing government regulations, such as accreditation requirements, economic crises, and pandemics further increase operational burdens. Aims. High patient expectations for service quality and pressure from the ASEAN Economic Community (AEC) compel clinics to adapt and survive. To address these challenges, clinics need an Early Warning System (EWS) integrated within the Clinic’s Early Warning System Framework (CEWSF). Methods. The research methods used are descriptive survey and methods Explanatory Survey. Result. CEWSF maps the risks faced by clinics, including financial, health, legal, operational, reputational, and environmental risks, all integrated into a digital information system. However, many clinics, especially smaller ones, do not yet have a Financial Early Warning System (FEWS) to identify and prevent risks. The absence of FEWS leads to slow responses to financial issues. Conclusion. Implementing technology-based EWS, such as data analysis and artificial intelligence, is crucial for maintaining clinics' operational continuity. Implementation. While some countries have adopted FEWS, Indonesia has yet to have hospitals that comprehensively embrace this framework.